Clinical forms of 5 cases of circumcised penile cancer in immunocompetent subjects in Abidjan (Ivory Coast) - Evrard Kouame Yao; Abraham Hognou Yao; Donafologo Daouda Yeo; Tawakaltu Adebayo; Michel Tuo; Freddy Junior Zouan; Noel Coulibaly (Basic and Clinical Andrology)
Abstract Context Malignant tumours of the penis are rare. Their incidence varies around the world and increases with age. Treatment is essentially surgical. Surgery may be conservative or radical. We report the anatomoclinical aspects of 5 cases of penile cancer observed in our department. Case presentations A 44-year-old patient with a circumcised penis, diagnosed with a fusosarcoma (a rare type of sarcoma) of the penis. Three patients (ages 61, 59, and 70) were diagnosed with squamous cell carcinoma, the most common type of penile cancer. These patients also had circumcised penises. The last case was a metastatic squamous cell carcinoma of the penis in a 68-year-old patient. All patients were immunocompetent and had a circumcised penis. They refused surgery in any form. Conclusion The clinical aspects of penile cancer are polymorphous and misleading. Any bulging or indurated lesions on the penis should be biopsied.